2 - Developing Mechanisms to Promote South-South Research in Science and Technology: the Case of the Southern African Development Community - Michael J. Kahn (African Sociological Review, 2001)
The African continent has struggled ta develop an indigenous agenda for science and technology research and development. Despite efforts since the 1960s, the results have been less than satisfactory. In the southern region, the Southern African Development Community (SADC) has attempted to play a coordinating rote for science and technology, but is widely regarded ta have been unsuccessjul in this venture. Although many countries in the SADC region have elevated the science and tech nology (S&T) function to Ministerial level, the linkages between S&T, government, industry and higher education are tenuous atbest. There has been much talk of policy driven development, but little in the way of action. This paper will sketch the history of S&T development in the SADC region and in particular the interplay between the local agenda and that of the advanced industrial countries. lt will highlight the difficul ties ofconducting research against imbalances in resources and exper tise by considering an initiative of the Department of Arts, Culture, Science and Technology that seeks to foster research cooperation between South Africa and the SADC region. The paper will explore the relations between and among state research institutions, higher educa tion and industry in SADC and considers possibilitiesfor local research co-operation.